Complementary alternative medicine use among patients with dengue fever in the hospital setting: a cross-sectional study in Malaysia - Siew, Mooi Ching; Ramachandran, Vasudevan; Lai, Teck Gew; Mohd Sazlly Lim, Sazlyna; Wan Sulaiman, Wan Aliaa; Yoke, Loong Foo; Zakaria, Zainul Amiruddin; Samsudin, Nurul Huda; Chih Lau, Paul Chih Ming; Veettil, Sajesh K.; Hoo, Fankee (BioMed Central, 2016)
BACKGROUND: In Malaysia, the number of reported cases of dengue fever demonstrates an increasing trend. Since dengue fever has no vaccine or antiviral treatment available, it has become a burden. Complementary and alternative medicine (CAM) has become one of the good alternatives to treat the patients with dengue fever. There is limited study on the use of CAM among patients with dengue fever, particularly in hospital settings. This study aims to determine the prevalence, types, reasons, expenditure, and resource of information on CAM use among patients with dengue fever.